Stress-Induced Polarization-Maintaining Large-Mode-Area Photonic Crystal Fibers With Deviation of the Single-Mode Transmission Band and Delocalization of Higher-Order Modes - Yuan Ma; Rui Wan; Huanhuan Yang; Yanfu Li; Chao Chen; Pengfei Wang (IEEE Photonics Journal, 2024)
The nonlinear effects and laser-induced optical and thermal damage in optical fibers, together with the limitations of beam quality and mode-field area, restrict the power scaling-up of single-mode output for developing high-power fiber lasers in the kilowatt and above range. The design of photonic crystal fibers (PCFs) with large mode areas is an effective way to address this problem. In this paper, the demands and challenges of designing very large-mode-area (VLMA-) PCFs are discussed, including the overall fiber structure design and property simulation, especially the precise definition of single-mode operating conditions of VLMA-PCFs. Finally, an advanced stress-induced polarization-maintaining, Yb-doped, PCF structure with a large mode area realized by introducing both leakage channels and higher order mode-filtering units is proposed and analyzed theoretically, for which a maximum core diameter of 101 $\boldsymbol{μ}{\text{m}}$ and single-mode field diameter of 76.33 $\boldsymbol{μ}{\text{m}}$ at 1064 $\text{nm}$ and a birefringence value $\boldsymbol{> 10^{-4}}$ orders of magnitude are achieved.